KEPEMIMPINAN, KOMPETENSI DAN KINERJA PENGARUHNYA TERHADAP PENGEMBANGAN KARIR APARATUR DI KOTA PALEMBANG - Dewi, Atika; Zamzam, Fakhry (Universitas Indo Global Mandiri Palembang, 2019)
This research discussed Leadership, Competence and Performance on civil servants’ Career Development in Palembang City. With the aim of whether or not there was an influence of Leadership, Competence and Performance on civil servants’ Career Development in Palembang City. The population used in this research was Civil Servants (ASN) at the Secretariat Staff in the Government of Palembang City. The sample in this research was 100 respondents. The data analysis technique used was Structural Equation Modeling (SEM). The results of test proved that: 1). Partially the results revealed that there was a significant and positive influence between Leadership, Competence and Performance on civil servants’Career Development in the City of Palembang.2). Simultaneously Career Development was influenced positively and significantly by the Leadership variable, Competence and Performance.Keywords:leadership, competence, performance, civil servants’ career development, Palembang city.